"The Letters of Cinnamon Shops": Bruno Schulz in the Reading of Serhiy Zhadan - Меньок, Віра (Київського національного університету імені Тараса Шевченка, 2025)
The author of the article focuses on the genesis, contexts and interpretative description of the texts by Serhiy Zhadan – the most important Ukrainian poet today – related to the work and figure of Bruno Schulz, including three essays, currently published only in Polish translation (“Drohobych and Its Surroundings”, “Schulz: Visions and Echoes”, “Artist In Wartime – Schulz Lost and Salvaged”) and the cycle of poems “Schulz. Psalms” from the poet’s latest volume “Skrypnykivka” (2023). The conceptual framework and narrative impulse of Schulz’s themes in Zhadan’s oeuvre is a poet’s regular participation in the International Bruno Schulz Festival (SchulzFest) held in Drohobych since 2004 on a biennial basis. The volume of poems Drohobych (2018), which exists only in the Polish edition, translated by Jacek Podsiadło, opens the presence of Schulz and Drohobych in Zhadan’s thinking and imagination as an autonomous literary project. After his first encounter with Drohobych, he confesses that he will always read this city in “the letters of cinnamon shops” – he was the first to encounter Schulz’s shadow there, which constantly returns. Zhadan suggests that one should not cry for Schulz’s worlds – one should believe in them, and during the war he speaks of Schulz lost and salvaged, of burned letters and lost manuscripts, of the defenselessness of art in the face of horror and of its saving power. The author of the article focuses on the interpretative discovery and interpretation of dramatic and figurative wholes, poetic and philosophical meanings, and contextual and intertextual traces that Serhiy Zhadan embodies in his reading of Bruno Schulz’s figure and literary heritage; invites to reflect on Schulz’s return and living presence in Zhadan’s texts, on the feeling of kinship with the genius who became a victim of the Holocaust and is now reborn in memory thanks to the psalmical power of the poet’s word, on the fascinating and sometimes unexpected paths of reading Schulz’s Drohobych “in the letters of cinnamon shops”. The author interprets Zhadan’s three unpublished essays in Ukrainian about both Schulz and Drohobych and his cycle of poems “Schulz. Psalms” as an exceptional literary whole with powerful interpretive potential in which symbolic figures and poetic insights from different times are intertwined, including intentional and immanent affinities and echoes not only with the author of “Cinnamon Shops”, but also with Paul Celan, Jerzy Ficowski, Ryszard Krynicki, and Rainer Maria Rilke. The article touches on the deep and vast space of Zhadan’s texts dedicated to Schulz, with the literary and extra-literary traces as well as meanings revealed in this space.

Авторка розвідки зосереджується на ґенезі, контекстах та інтерпретаційних описах текстів Сергія Жадана – найважливішого нині українського поета, – пов’язаних із творчістю й постаттю Бруно Шульца, а саме: три есеї, наразі опубліковані лише у польських перекладах («Дрогобич та околиці», «Шульц: видіння і відлуння», «Митець у часи війни: Шульц утрачений і збережений») та цикл «Шульц. Псалми» з найновішої збірки віршів поета «Скрипниківка» (2023). Концептуальною основою та наративним імпульсом для шульцівської тематики у творчості Жадана є його тягла участь у Міжнародному Фестивалі Бруно Шульца (ШульцФест), який відбувається у Дрогобичі від 2004 року у дворічному циклі. Збірка віршів «Дрогобич» (2018), яка існує лише у польському виданні, у перекладі Яцека Подсядла, відкриває присутність Шульца та Дрогобича у поетичному мисленні й уяві Жадана як автономного літературного проєкту. Після першої зустрічі з Дрогобичем поет визнає, що завжди читатиме це місто «літерами цинамонових крамниць» – першою зустріла його тут тінь Шульца, яка безнастанно повертається. Жадан закликає не оплакувати світи Шульца, лиш вірити у них, а в часи війни говорить про втраченого й урятованого Шульца, про спалені листи й знищені рукописи, про беззахисність мистецтва перед обличчям жахіття і водночас про його рятівну силу.
«Літерами Цинамонових крамниць»: Бруно Шульц у прочитанні Сергія Жадана
Keywords: Serhiy Zhadan; Bruno Schulz; SchulzFest; Drohobych; essays; psalms; horror; salvation; Сергій Жадан; Бруно Шульц; ШульцФест; Дрогобич; есей; псалми; жахіття; зцілення